“Russian Palladio”: Palladianism as a Mechanism of Adoption of the Classical Heritage in the 20th Century Russian Architecture - Bass, Vadim G. (Actual Problems of Theory and History of Art, 2015)
Palladianism was the necessary element of neoclassical waves in Russian architecture — from the 1900/10s through 1930/50s up to nowadays. What determined the popularity of Palladio? First of all, the architect’s belief in law underlying the form. Order as the paradigm of proportionality was the embodiment of this law. The specific character of “Four books…” also contributed to his popularity. This treatise was to some extent the practical builder’s manual for both trained architects and laymen. There was also another reason for Palladio’s attractiveness: along with the Classicist, there was also Mannerist Palladio. The former longs for law while the latter individualizes the expression of this law in a particular building. The “demand for Palladio” also resulted from the cultural isolation from the antique sources. This kind of art lost its relation with the reality and history. Imitation of history needs fake architecture, so Palladio was the right person to do the task.